Effect of Different Ratios of Red and Blue Light on Maximum Stomatal Conductance and Response Rate of Cucumber Seedling Leaves - Xue Li; Shiwen Zhao; Aiyu Lin; Yuanyuan Yang; Guanzhi Zhang; Peng Xu; Yongjun Wu; Zhenchao Yang (Agronomy, 2023)
Light can regulate leaf stomatal development and movement, but the effects of different red-to-blue light mass ratios on leaf stomatal morphology and openness are not fully understood. In this trial, five different red-to-blue light (R:B) ratio treatments were used to study the changes in morphology, photosynthesis, and stomatal-related indexes of cucumber seedlings under fixed light intensity (200 μmol·m−2·s−1). The results showed that the thickness of spongy tissue and stomatal size (SZ) of cucumber seedling leaves decreased, and the photosynthetic potential, stomatal density (SD), maximum stomatal conductance and stomatal responsiveness increased with decreasing R:B content. The experimental results showed that when R:B = is 1:9, cucumber seedlings had the greatest stomatal density and the fastest response rate, and the stomatal opening rate was accelerated with the increase in the proportion of blue light; when R:B = is 3:7, the stomatal conductance was the greatest and the net photosynthetic rate was the highest. This trial provides some implications for changing plant light quality and thus affecting stomatal development and movement.